Children's interpretation of epithets: On coreference and self-ascription. - Brunetto, Valentina (Language Acquisition)
The debate around the delayed acquisition of Condition B (the 'DPBE stage') has traditionally focused on the local coreference rule (Rule I) which regulates the competition between binding and coreference. In adult grammars, this rule sanctions Condition B obviations with a restricted class of predicates: intensional transitives like adore, praise, and exceptional case marking (ECM) verbs like see. Grodzinsky proposed that locally coreferential pronouns are licit when they signal non-self-ascriptive perspective. This hypothesis was investigated in child Italian (N = 38, age 4-6 years) by testing a class of nominals which is overtly specified for speaker-oriented perspective: epithets, such as the rascal. Children were tested in two Truth-Value Judgment tasks: task 1 tested epithets in local (intensional transitive) and non-local (attitude) domains; task 2 compared epithets and clitics in ECM sentences. Children's performance with clitic pronouns in the ECM task (an indicator of DPBE in Italian) predicted their interpretation of epithets: only children in the DPBE stage were at chance in blocking local coreference with epithets, but all children performed at chance with epithets inside attitude clauses. This is the first empirical study to show that epithets are subject to a DPBE in child grammar. It is suggested that children's ability to enforce competition between nominals interacts with the acquisition of self-ascriptive perspective.